Different COVID19 pandemic phases & STEMI: experience from an Italian hub centre. (14th October 2021) - Tumminello, G; Barbieri, L; Toriello, F; Lucreziotti, S; Carla', M; Conconi, B; Salerno Uriarte, D; Mafrici, A; Carugo, S
Abstract: Introduction and methods: During Coronavirus disease 2019 (COVID-19) pandemic a reduction in ST-elevation acute myocardial infarction with an increase in in-hospital mortality has been observed. In our region the pandemic temporal trend was sinusoidal with peaks and valleys. A first outbreak (phase-peak 1 "P-P1") was in March 2020 (248.12 cases for 100, 000 inhabitants), a reduction (phase-valley 1 "P-V1") in May 2020 (16.68 cases for 100, 000 inhabitants) and a second outbreak (phase-peak 2 "P-P2") in November 2020 (540.17 cases for 100, 000 inhabitants; data from Italian Health Ministry). Our hospital was reorganized as one of the 13 Macro-Hubs identified in Lombardy for the treatment of STEMI. Here we describe our experience in the treatment of STEMI patients in the three different phases of COVID-19 pandemic. Results: In the three different phases the groups were superimposable for mean characteristics, but they differ for COVID-19 infection incidence (table). At multivariate analysis for the entire population COVID-19 infection (OR 45.8 [95% CI] 1.39–1511.79; p=0.03) was the only independent predictor of in-hospital mortality. Focusing on COVID-19 patients (figure) they experienced a 5-time increased incidence of in-hospital mortality (COVID-19pos vs COVID-19neg, 50% vs 11.1%; p=0.02). Moreover, the compresence of COVID-19 infection induced an 8 times increased risk of death (OR 8; [95% CI] 1.85–34.60; p=0.005) determined by a higher incidence respiratory complications (COVID-19pos vs COVID-19neg, 33.3% vs 8.9%; p=0.03) with a similar incidence of cardiac death (COVID-19pos vs COVID-19neg, 16.7% vs 11.17%; p=0.60). Conclusions: In conclusion our data suggest the crucial necessity of an early and precise diagnosis of COVID-19 infection in STEMI to establish a correct management of this very high risk patients. FUNDunding Acknowledgement: Type of funding sources: None.